2020
DOI: 10.3389/fnagi.2020.00067
|View full text |Cite
|
Sign up to set email alerts
|

Exosome α-Synuclein Release in Plasma May be Associated With Postoperative Delirium in Hip Fracture Patients

Abstract: Background:Little is known about the underlying mechanisms of the similarities in the core features of postoperative delirium (POD) and α-synuclein (α-syn)-related cognitive disorders. We herein investigated associations between fluctuated levels of exosomal α-syn in the plasma and POD presentation in geriatric hip fracture patients. Methods:We conducted an observational, prospective, and 1:1 matched (on age older than 65, hip fracture diagnosis, American Society of Anesthesiologist' (ASA) physical status, dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Moreover, α -syn can also impair the NMDA receptor-mediated LTP, an enhanced synaptic activity, which is widely accepted to be related to memory formation [ 46 ]. Meanwhile, our preliminary studies [ 15 , 16 ] and others [ 17 , 18 ] have demonstrated that α -syn may also be associated with surgery-induced cognitive impairment. However, the exact association between α -syn accumulation and the mechanism of dNCR is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, α -syn can also impair the NMDA receptor-mediated LTP, an enhanced synaptic activity, which is widely accepted to be related to memory formation [ 46 ]. Meanwhile, our preliminary studies [ 15 , 16 ] and others [ 17 , 18 ] have demonstrated that α -syn may also be associated with surgery-induced cognitive impairment. However, the exact association between α -syn accumulation and the mechanism of dNCR is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Aggregation and propagation of misfolded α -syn in the brain are involved in the pathogenesis of neurodegenerative diseases, especially in Parkinson's disease cases [ 13 , 14 ]. In our earlier work, we demonstrated that anesthesia and surgery increased α -syn oligomerization and disturbed neurotransmitter homeostasis in the hippocampus of aged rats, while exosome α -syn release into the plasma of postoperative delirium (POD) patients with hip fractures was significantly higher compared with non-POD cases [ 15 , 16 ]. In addition, an earlier study from another laboratory found elevated total α -syn expression in the cortex after 12 h, with attention deficit after 24 h in mice following anesthesia plus surgery [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increase of pro-inflammatory factors like TNF-α, IL-1β and IL-6 is positively related to POD pathogenesis. 23–26 The up-regulated inflammatory response has been also demonstrated in POD animal model studies. 7 , 27 , 28 In this study, human recombinant MANF inhibited the surgery-induced inflammatory response in mice to decrease the surgery-induced increase of IL-1β, IL-6 and TNF-α in serum and pre-cortex of mice brain, suggesting that MANF up-regulation in circulation and brain might be a self-protective response to surgery.…”
Section: Discussionmentioning
confidence: 91%
“…The pathogenesis of PND is multifaceted, which might be associated with anesthesia, tissue damage, neuroinflammation, surgical stress, psychological stress, and so on. In human studies, patients who develop PND showed cerebrospinal fluid (CSF) and plasma pro-inflammatory cytokines increases after anesthesia and surgery (Ji et al, 2013 ; Hirsch et al, 2016 ; Yuan et al, 2020 ). The more pronounced changes in CSF cytokines compared to plasma for several cytokines (MCP, MIP-1α, MIP-1β) provide evidence for substantial inflammatory activity in the CNS (Hirsch et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The more pronounced changes in CSF cytokines compared to plasma for several cytokines (MCP, MIP-1α, MIP-1β) provide evidence for substantial inflammatory activity in the CNS (Hirsch et al, 2016 ). Since microglia are the macrophages of the CNS and play critical roles in neuroinflammatory disease (West et al, 2019 ), the significant alterations in some cytokines in CSF from patients indicate that microglia may be involved in PND in human (Helmy et al, 1999 ; Bromander et al, 2012 ; Hirsch et al, 2016 ; Yuan et al, 2020 ). Mounting evidence from animal studies suggests that microglia, like immune cells, are activated in the CNS and implicated in neuroinflammation and PND.…”
Section: Introductionmentioning
confidence: 99%